Detecção dos Isotipos IgM, IgA e IgG na infecção pelo vírus do Dengue e sua reatividade aos sorotipos virais DEN-1, DEN-2 e DEN-3 - Carvalho, Cinthia Barbosa de (2004)
Dengue is currently the most important arbovirus disease that affects humans and it constitutes a serious problem of public health in the world, mainly in the tropical countries. The aim of this study was to determine dengue-specific IgM, IgA, and IgG leveis by capture immunoenzymatic assays (MAC-, AAC-, and GAC-ELISA, respectively) and to analyze their reactivity to dengue serotypes (DEN-1, DEN-2, DEN-3). A total of 504 serum samples from patients with symptoms suggestive of dengue vírus infection were randomly chosen among samples collected and sent to the Immunology Laboratory in 1997, 2000, and 2003, in Uberlândia, MG, Brazíl. Positivity rates for all isotypes increased significantly from 1997 to 2003. IgM and IgG leveis were higher than IgA in 1997 and 2003, whereas isotype leveis were not significantly different in 2000, when lower leveis of IgM and IgG were found. Overall, the antibody leveis detected by MAC-, AAC-, and GAC-ELISA showed a strong positive correlation in the studied years, but when analyzing only the reactive samples, a significant positive correlation was solely found for IgG and IgA. Concerning the degree of reactivity for dengue serotypes, noteworthy differences were observed during the time of this study. DEN-2 was the major serotype for all isotypes in 1997, while both DEN-2 and DEN-3 were the predominant serotypes for all isotypes in 2000. However, in 2003, a significant modification was observed in the pattern of reactivity to viral serotypes, when DEN-3 became the predominant one for all studied isotypes. Altogether, it can be concluded that the measurement of dengue-specific isotype leveis and their differential reactivity to viral serotypes can supply useful information about the different stages of infection, contributing to the establishment of appropriate treatment and decreasing the probability of fatal disease.